Biliary cystadenoma and choledochal polyp: a rare association - A.Y. Lakshmi; B.Vijayalakshmi Devi; P. Sriram; M. Kumaraswamy Reddy (Journal of Clinical and Scientific Research, 2013)
Biliary cystadenomas are rare, potentially malignant neoplasms of biliary origin occurring predominantly in middle aged women. Here we report a case of biliary cystadenoma in a young female who presented with an epigastric mass and features of obstructive jaundice. Imaging studies showed a mass in the left lobe of liver with dilated intra hepatic biliary ducts, right hepatic duct and common bile duct. Patient was subjected to left hepatectomy and hepatico-jejunostomy. Histopathology confirmed the lesion as biliary cystadenoma with choledochal polyp.